Perancangan Mebel Modular Edukatif Untuk Anak Balita (Studi Kasus: Sekolah Minggu di Greja Kristen Jawi Wetan Jemaat Sukolilo Surabaya) - Ervinna Ervinna; Andereas Pandu Setiawan; Poppy Firtatwentyna Nilasari (Intra, 2018)
Toddlers are children who have reached the age of 1 year or under 5 years of age. Toddlers are also include children aged 1-3 years, and pre-school children (aged 3-5 years). From an early age, children should be provided with spiritual education such as the Greja Kristen Jawi Wetan Jemaat Sukolilo Surabaya’s Sunday school program, where children can establish a new social circle. The design method used in this project is design thinking method, which includes survey to the Sunday school’s location, interview with the Sunday school teachers, measure the furniture and room sizes, programming analysis, schematic design, final design, 1:10 mock model and 1:1 prototype realization. Therefore, the results of design is an educative modular furniture for toddlers with knock-down system that is beneficial for the process of Sunday school activities and able to accommodate the activities of toddlers. The modular furniture also equipped with a game area with storage to introduce shapes and colors to the children.